PENGARUH KESADARAN PERPAJAKAN, SANKSI PAJAK DAN TAX AMNESTY TERHADAP KEPATUHAN WAJIB PAJAK ORANG PRIBADI - Nahdah Fistra Karnedi; Amir Hidayatulloh (Fakultas Ekonomi Dan Bisnis, Universitas Mercu Buana, Jakarta, 2019)
This study aims to determine the effect of taxpayer awareness, tax sactions, and tax amnesty on individual taxpayer compliance. The population in this study are individual taxpayer who dominate in Yogyakarta city. The sample in this study are an individual taxpayer who dominate in Yogyakarta city and conduct tax amnesty. The sampling technique in the study was pusposive sampling, with criteria of taxpayer participation in the tax amnesty. The data analysis technique in this study uses multile linear regression. This study found that individual taxpayer compliance is influenced by tax saction and tax amnesty. Whereas, awareness of taxpayer does not affect individual taxpayer compliance